Florid Granuloma Annulare–Like Reaction in Regional Lymph Nodes After "Regression" of Red Pigment in Tattoos. (May 2018) - Carter, Michael D.; Trites, Jonathan; McNeil, Shelly A.; Walsh, Noreen N. M.; Bullock, Martin J.
Abstract : Abstract: A healthy 50-year-old woman had a tattoo performed on the posterior aspect of her neck and another on the dorsum of her left foot. Several weeks later, she noted redness, tenderness, and intense pruritis at both tattoo sites. Treatment with cephalexin and hydrocortisone cream was instituted, without success. Within a few months, the red, but not black, pigment had disappeared from both tattoos and was replaced by pale areas of scarring. Persistently enlarged left supraclavicular and suboccipital lymph nodes were excised 7 and 10 months after receipt of the tattoos, respectively. The nodes were pigmented on gross examination, and on microscopy, a granuloma annulare–like reaction was observed. Normal lymphoid tissue was seen to be replaced by large palisading granulomas with central degenerative change, abundant stromal mucin, and scattered deposits of tattoo pigment. Histochemical stains, tissue culture, and serological studies revealed no evidence of infection. There are rare reports of granuloma annulare–like reactions in tattoos, and these are believed to represent delayed-type hypersensitivity reactions. Our case is unique in the observation of this reaction pattern in regional lymph nodes, and it expands the spectrum of complications known to be associated with tattoos.